Gender Gaps and Racial Disparities in Labour Market Penalties for Financial Misconduct - Jun Honda (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
We consider the labour market for financial advisers in the US using a matched employer-employee data set over the period 2008-2018, in order to examine gender gaps and racial disparities in labour market penalties for financial misconduct. We first show that the measurement of labour market penalties for financial misconduct plays a central role and the interdependence across misconduct-categories (e.g. customer disputes, regulatory actions, terminations) is gender- and racespecific. Accounting for this, we find that there are little gender gaps in job separation following misconduct and in the incidence of employer-initiated terminations conditional on misconduct-related events. In contrast, we find that racial minorities are at least 20% more likely to leave a firm following customer disputes or regulatory actions compared to their majority counterparts, and also that the racial minorities are 25% more likely to receive terminations. This remains true even after controlling for their education.
Keywords: G24; J44; J71; L22; 330; Financial Advisers; Misconduct; Gender Gap; Racial Inequality; Discrimination